Risk factors for the development of antibody‐mediated rejection in highly sensitized pediatric kidney transplant recipients. (19th September 2017) - Kim, Irene K.; Choi, Jua; Vo, Ashley; Kang, Alexis; Steggerda, Justin; Louie, Sabrina; Haas, Mark; Mirocha, James; Cohen, J. Louis; Pizzo, Helen; Kamil, Elaine S.; Jordan, Stanley C.; et al.
Abstract: ABMR remains a significant concern for early graft loss, especially for those who are HS against HLA antigens. We sought to determine the risk factors leading to ABMR in HS pediatric kidney transplant recipients. From January 2009 to December 2015, 16 HS pediatric kidney transplant patients at our center (age range 2‐21) were retrospectively reviewed for outcomes and risk factors for ABMR. All HS patients received desensitization with high‐dose IVIG/rituximab prior to transplant. Two groups were examined: ABMR + (n = 7) and ABMR − (n = 9). Patient survival was 100%; however, one patient in the ABMR + group suffered graft loss from ABMR 16 months post‐transplant. ABMR + patients had higher Class I PRA at the time of transplant (Class I: 73.1 ± 19.1 vs 49.1 ± 28.3, P  = .075), although not statistically significant. ABMR + patients were more likely to have a history of transplant nephrectomy ( P  = .013). The characteristic that most strongly correlated with ABMR was the DSA‐RIS ( P  = .045), a scoring system used to quantify cumulative intensity of all DSA. In conclusion, DSA, as quantified by the RIS at the time of transplant, should be considered as part of the initial allocation strategy and patients with high RIS monitored closely for ABMR post‐transplant.